Homofobia na educação : estudo de caso comparativo entre duas escolas de Londrina - PR - Moreira, Leandro (2015)
This text aims to analyze and understand the role of educational institution forward intolerance practices and discrimination LGBT and know the social reality of school before such practices. In this sense, said research is to check to what extent the school works to denature or not, deeply consolidated views on homosexuality and homophobia. To do so, depart methodology document analysis and case study. The document analysis will research laws, actions and public policy at the federal level, the Ministry of Education, and state of Paraná State Department of Education, from the beginning of the Republic in Brazil until today. The case study, in situ, was carried out with teachers and students from two schools in the public schools of the city of Londrina-PR. Two distinct schools were chosen, one located in the central region and taken as a reference and the other on the outskirts of the city. This choice was in order to ascertain the perception of respondents about homosexuality and homophobia and also the specifics as to the learning on this topic. Since this is a new theme, set recently in the gym, the theoretical basis is anchored in contemporary authors who discuss: sexuality and gender, homophobia, discrimination, sexual diversity, LGBT and all these issues correlated to: public education, curriculum, school and teacher training in Brazil. The data reveal that there is an exacerbation of prejudice occurring in school, it shows how homophobia is linked to the limited education of public school and she is unable to change and significant changes in the line of thought, behavior, customs and values thus the school is not fulfilling the role which was assigned to him.